The role of VDR and TNF gene polymorphism in cytokine regulation in type I diabetes mellitus of the Uzbek population, Samarkand, Uzbekistan - FARIZA RAYIMOVA; GAVHAR DUSHANOVA; BEGALI ALIKULOV; ZAYNITDIN KAMALOV; MALIKA RUZIBAKIEVA; FARANGIZ NABIYEVA; ASATILLO RAJABOV (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Rayimova F, Dushanova G, Alikulov B, Kamalov Z, Ruzibakieva M, Nabiyeva F, Rajabov A. 2024. The role of VDR and TNF gene polymorphism in cytokine regulation in type I diabetes mellitus of the Uzbek population, Samarkand, Uzbekistan. Biodiversitas 25: 1329-1336. After 2000, diabetes became one of the most common diseases in the world. Special attention is paid to the research to determine the variability of genetic processes in patients in the origin and development of this disease. The article is devoted to the study of the connection between the polymorphism of genotypes GG, GA, AA polymorphism BsmI of the VDR- (Vitamin D receptor) gene and GG, GA of the TNF-A-308G/A- (Tumor necrosis factor A) gene with the regulation of cytokines TNF? and IL6-Interleykin 6 in sick and healthy individuals of the Samarkand region of the Uzbek population. The analysis of the BsmI polymorphism of the VDR gene and TNF-A-308G/A indicates the involvement of certain genotypes in the Type 1 Diabetes Mellitus (T1DM) pathogenesis. The age of onset of the disease in the studied population is from 7 years, but the increase in the incidence of diseases begins from 10 years. Type 1 diabetes is more common in females. Studies of the relationship between the cytokines TNF? and IL6 show their high content depending on the genotypes GG, GA, and AA of the BsmIA polymorphism of the VDR gene and the genotypes GG and GA of the gene. TNF-A-308G/A. However, the highest rates were recorded in individuals with the AA genotype of the BsmI polymorphism of the VDR gene. The obtained results can serve as fundamental knowledge in revealing and explaining the mechanisms of cytokinin control in people with diabetes in different populations of the same nation.